Higher Intake of Polyunsaturated Fatty Acid and Monounsaturated Fatty Acid is Inversely Associated With AMD - Roh, Miin (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To evaluate the association between dietary fat intake and the presence of AMD. METHODS: Cross-sectional, observational study with cohorts prospectively recruited from the United States and Portugal. AMD was diagnosed based on color fundus photographs with the AREDS classification. A validated food frequency questionnaire was used to calculate the percent energy intake of trans fat, saturated fat, monounsaturated fatty acid (MUFA), and polyunsaturated fatty acid (PUFA). Odds ratio (OR) and 95% confidence intervals for quintile of amount of FA were calculated. Multiple logistic regression was used to estimate the OR. RESULTS: We included 483 participants, 386 patients with AMD and 97 controls. Higher intake of trans fat was associated with a 2.3-fold higher odds of presence of AMD (P for trend = 0.0156), whereas a higher intake of PUFA (OR, 0.25; P for trend = 0.006) and MUFA (OR, 0.24; P for trend < 0.0001) presented an inverse association. Subgroup analysis showed that higher quintile of trans fat was associated with increased odds of having intermediate AMD (OR, 2.26; P for trend = 0.02); and higher quintile of PUFA and MUFA were inversely associated with intermediate AMD (OR, 0.2 [P for trend = 0.0013]; OR, 0.17 [P for trend < 0.0001]) and advanced AMD (OR, 0.13 [P for trend = 0.02]; OR, 0.26 [P for trend = 0.004]). Additionally, a statistically significant effect modification by country was noted with inverse association between MUFA and AMD being significant (OR, 0.04; P for trend < 0.0001) for the Portugal population only. CONCLUSIONS: Our study shows that higher dietary intake of trans fat is associated with the presence of AMD, and a higher intake of PUFA and MUFA is inversely associated with AMD.